Risk factors for episodes of back pain in emerging adults. A systematic review. (3rd September 2019) - Øiestad, Britt Elin; Hilde, Gunvor; Tveter, Anne Therese; Peat, George G.; Thomas, Martin J.; Dunn, Kate M.; Grotle, Margreth
Abstract: Background and Objective: The transition from adolescence to adulthood is a sensitive period in life for health outcomes, including back pain. The objective was to synthesize evidence on risk factors for new episodes of back pain in emerging adults (18–29 years). Methods: The protocol was registered in PROSPERO (CRD42016046635). We searched Medline; EMBASE; AMED and other databases up to September 2018 for prospective cohort studies that estimated the association between risk factor(s) and self‐reported back pain. Risk factors could be measured before or during the age range 18–29 years, and back pain could be measured during or after this age range, with at least 12 months between assessments. Risk factors assessed in ≥3 studies were summarized. Risk of bias was assessed using a 6‐item checklist. Results: Forty‐nine studies were included with more than 150 different risk factors studied. Nine studies had low risk of bias, 26 had moderate and 14 had high risk of bias. Age, sex, height, body mass index (BMI), smoking, physical activity level, a history of back pain, job satisfaction and structural imaging findings were investigated in three or more studies. History of back pain was the only risk factor consistently associated with back pain after adjustment (nine studies). Conclusion: There is moderate quality evidence that a history of back pain is a risk factor for back pain. There are inconsistent associations for age, sex, height, BMI, smoking and activity level. No associations were found between job satisfaction and structural imaging findings and back pain. Significance: Emerging adulthood is a transitional period of life with changes in life style, potentially influencing future musculoskeletal health. This systematic review included 49 articles evaluating more than 150 potential risk factors for back pain, one of the most prevalent musculoskeletal disorders. No consistent results were found for life style factors such as physical activity level or BMI, both highlighted as important risk factors in previous literature. Importantly, a previous episode of back pain was a consistent risk factor for a new episode of back pain across several studies, and further investigation of risk factors for the first back pain episode is needed.